2020
DOI: 10.3389/fonc.2020.550673
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-Methylacyl-CoA Racemase (AMACR), a Potential New Biomarker for Glioblastoma

Abstract: Alpha-Methylacyl-CoA racemase (AMACR), which was initially discovered as a prostate cancer marker, is critical for the chiral inversion mechanism of branched-chain fatty acids. However, the function of AMACR in brain tumors has not been investigated. In this study, AMACR appeared to be involved in glioblastoma. The protein and mRNA levels of AMACR were highly elevated in glioblastoma. Downregulation of AMACR inhibited cell proliferation. Comprehensive analysis of the public REMBRANDT GBM dataset also confirmed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 12 publications
2
18
0
Order By: Relevance
“…AMACR expression is high in several types of cancers (Thul et al, 2017), including gastric cancer (Nozawa et al, 2012), ovarian cancer (Noske et al, 2011), renal cell carcinoma (Eichelberg et al, 2013), and hepatocellular carcinoma (Figure 3; Yu et al, 2019). Increased expression of AMACR also affects the survival of cancer patients (Figure 4; Lee, 2019). We also confirmed the expression of AMACR in human glioblastoma cell lines (U87-MG, U251-MG, U343-MG, and U373-MG) (Figure 5).…”
Section: Amacr Function In Cancersupporting
confidence: 60%
“…AMACR expression is high in several types of cancers (Thul et al, 2017), including gastric cancer (Nozawa et al, 2012), ovarian cancer (Noske et al, 2011), renal cell carcinoma (Eichelberg et al, 2013), and hepatocellular carcinoma (Figure 3; Yu et al, 2019). Increased expression of AMACR also affects the survival of cancer patients (Figure 4; Lee, 2019). We also confirmed the expression of AMACR in human glioblastoma cell lines (U87-MG, U251-MG, U343-MG, and U373-MG) (Figure 5).…”
Section: Amacr Function In Cancersupporting
confidence: 60%
“…265 siRNA knock-down of AMACR levels led to reduced proliferation of glioblastoma cells. 265 Increased AMACR levels are thought to indicate an increase in fatty acid b-oxidation, in a similar way to that observed in prostate cancer. 266 AMACR has been the subject of several previous inhibitor studies as well as structural studies on the M. tuberculosis homologue (MCR), with literature up to the end of 2012 having been previously reviewed.…”
Section: Cofactor-independent Racemases and Epimerasesmentioning
confidence: 94%
“… 263 Interestingly, a recent epidemiological study showed that AMACR levels were diminished in men with prostate cancer who supplemented their diet with extracts from cruciferous vegetables, such as broccoli, which contains the isothiocyanate compound, sulforaphane. 264 AMACR levels are also increased in glioblastoma 265,266 and high AMACR levels are correlated with poor prognosis for patients. 265 Hence, AMACR is a potentially a novel biomarker for glioblastoma.…”
Section: Inhibitors Of Racemases and Epimerasesmentioning
confidence: 97%
See 2 more Smart Citations